Green procurement in the construction industry: unfolding new underlying barriers for a developing country context - Yap, Jeffrey Boon Hui; Teh, Yu Han; Loo, Siaw Chuing; Shavarebi, Kamran; Zamharira, Binti Sulaiman (Journal of Civil Engineering and Management, 2024)
Despite the construction industry’s detrimental effects on environmental sustainability, the concept of green procurement (GP) is still relatively new in the developing world. The barriers hindering GP adoption need detailed investigation as studies in the context of developing countries are still limited and the underlying dimensions remain a known-unknown. This study appraised the critical barriers to GP adoption in the Malaysian construction industry. Twenty (20) barriers were identified from the detailed literature review and a field survey was conducted with 150 professionals. The ranking analysis results indicated the top five barriers are: high initial cost; lack of expertise and regulations; lack of government regulations; lack of top management commitment and lack of awareness among construction stakeholders. A factor analysis further identified five major underlying dimensions. The study showed that both government and organisational commitments are crucial in promoting GP adoption. This study adds to incremental knowledge in GP literature by analysing the critical barriers and the associated underlying dimensions to GP adoption in a developing country, which could help practitioners and policymakers in evaluating the organisation’s or industry’s readiness to adopt GP practices along with devising apt measures to mitigate the barriers to shift to sustainable and environmentally friendly construction.